Analisis Kelayakan Kualitas Material Batu Pecah Dan Pasir Asal Kelurahan Wandoka Kecamatan Wangi-Wangi Kabupaten Wakatobi Sebagai Bahan Konstruksi Gedung - Muhsar, Muhammad; Sufrianto, Sufrianto; Hakiman, Hakiman; Hado, Hado (Universitas Sulawesi Tenggara, 2024)
Concrete is a construction material consisting of cement, fine aggregate, coarse aggregate which is mixed and added with sufficient water to form a dough which then hardens into hard concrete. This study aims to determine technical feasibility, the cost and the difference to the unit price based on the 2021 Regent's Regulation and to analyze the unit cost of construction of local Wakatobi materials and materials outside Wakatobi based on Analisa Harga Satuan Pekerjaan (AHSP). The method used in this study to determine the compressive strength of concrete refers to SNI 1974; 2011 and carried out observations and measurements in the laboratory with 60 specimens in the form of a cylinder with a diameter of 10 cm and a height of 20 cm with a concrete age of 28 days for each mixture variation. The results of the study obtained the compressive strength of aggregate variations on 100% Moramo coarse aggregate on crushed stone and sand with several variations. Comparison of the unit price of the Wakatobi local fine aggregate material with the outer Wakatobi fine aggregate material is 32.40% higher, the Wakatobi local coarse aggregate material unit price and the outer Wakatobi coarse aggregate material unit price is 52.17% higher. The construction unit cost for making 1 m3 of concrete using local Wakatobi materials is Rp. 1,916,756, and the construction unit cost for making 1m3 of concrete using non-wakatobi materials is Rp. 2,678,889. With a large construction unit, making 1m3 of concrete using external Wakatobi materials is 28.45% higher.